A Descriptive Study on Assessment of Functional Status in Cerebral Palsy Patients Using Knee Ankle Foot Orthosis - Arshad, Zeenat; Khan, Muhammad Kamran (Journal of Prosthetics Orthotics and Science Technology, 2024)
Background: Cerebral Palsy (CP) is the most prevalent motor disability in childhood, arising from abnormal brain development or damage, affecting muscle control. Knee Ankle Foot Orthoses (KAFO) is a lower limb orthosis extending from foot plate to thigh level, designed to support weakened leg muscles and stabilize knee and ankle joints, potentially halting deformity progression or rectifying flexibility. This study aims to elucidate the functional status of lower limb CP patients utilizing KAFO. Aims: This study aimed to describe the functional level of lower limb CP patients wearing KAFO. Methods: Informed consent was obtained, and data of 110 cerebral palsy patients were collected using non-random consecutive sampling. Patients were divided into two groups: one with 80 patients utilizing KAFO with 4PPS (four-point pressure system), and the other with 30 patients not using KAFO with 4PPS. Observational gait analysis was conducted, and subjective and objective details were recorded on a specially designed questionnaire. The OPUS scale evaluated the functional status of CP patients, and statistical analysis employed chi-square tests to examine the role of KAFO in their functional status using SPSS version 21.0. Results: Statistical analysis revealed a significant relationship between total functional score and KAFO use. Among the 80 KAFO users, 71 patients scored >40, while 9 scored <40. In the non-KAFO group, 28 patients scored <40, and 2 scored >40. KAFO users exhibited higher total functional scores, indicating improved functionality and independence in daily activities (p<0.05). Conclusion: The study concludes that KAFO utilization enhances the functional status of cerebral palsy patients, facilitating independent engagement in daily activities. Comparison of total scores between KAFO users and non-users underscores the association between functional improvement and KAFO use.